2017
DOI: 10.1021/acs.jcim.7b00431
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Changes the Mechanisms of Aβ Peptide Binding to the DMPC Bilayer

Abstract: Using isobaric-isothermal all-atom replica-exchange molecular dynamics (REMD) simulations, we investigated the equilibrium binding of Aβ10-40 monomers to the zwitterionic dimyristoylphosphatidylcholine (DMPC) bilayer containing cholesterol. Our previous REMD simulations, which studied binding of the same peptide to the cholesterol-free DMPC bilayer, served as a control, against which we measured the impact of cholesterol. Our findings are as follows. First, addition of cholesterol to the DMPC bilayer partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 67 publications
(171 reference statements)
7
33
0
Order By: Relevance
“…412 The sensitivity to cholesterol of different Aβ peptides has also been addressed by simulations describing different cholesterol hot-spots depending on their length. 765767 Cholesterol bound at the tandem glycine motif might compete with helix dimerization, 768 but other sites have also been proposed to promote helix–helix interactions. 769 More in general, the lipid environment and composition greatly affect helix orientation and dimerization of precursors of different lengths, 770,771 an aspect that has been addressed with MD simulations as well.…”
Section: C99 and γ-Secretasementioning
confidence: 99%
“…412 The sensitivity to cholesterol of different Aβ peptides has also been addressed by simulations describing different cholesterol hot-spots depending on their length. 765767 Cholesterol bound at the tandem glycine motif might compete with helix dimerization, 768 but other sites have also been proposed to promote helix–helix interactions. 769 More in general, the lipid environment and composition greatly affect helix orientation and dimerization of precursors of different lengths, 770,771 an aspect that has been addressed with MD simulations as well.…”
Section: C99 and γ-Secretasementioning
confidence: 99%
“…The molecular docking results showed that the U-shaped oligomers inserted into the membrane and formed ion-permeable pores [ 67 ], which is consistent with the report that Aβ can insert into lipid bilayers and assemble into a β-barrel pore under optimized detergent micelle conditions [ 68 ]. Aβos can also interact with lipids and cholesterol in the membrane to exert their toxicity [ 69 , 70 , 71 , 72 , 73 ]. For example, Aβos strongly bind to GM1 ganglioside located at the external face of the cell membrane to promote LTP impairment, which requires the existence of sialic acid residues of GM1 [ 71 ].…”
Section: The Neurotoxicological Mechanisms Of Aβosmentioning
confidence: 99%
“…The effect of cholesterol on the toxicity of Aβos to membrane is controversial. Cholesterol can change the structures of Aβos and facilitate the interaction between Aβ and the membrane, on the other hand, cholesterol increases the membrane rigidity and has a protective effect against Aβos-mediated damage [ 69 , 72 ].…”
Section: The Neurotoxicological Mechanisms Of Aβosmentioning
confidence: 99%
“…There are also contradictory data on the role of Chol in Aβ42-binding to bilayers, from those that suggest a positive role in Aβ42 binding and aggregation [19,38] to those who propose a negative influence [39] or a dual effect depending on Chol concentration [40]. In general, Chol appears to have a negative effect on Aβ binding and aggregation particularly in the absence of sphingolipids [41,42].…”
Section: Discussionmentioning
confidence: 99%